PERBANDINGAN KETERAMPILAN BERPIKIR KRITIS SISWA DENGAN MODEL PROBLEM-BASED LEARNING DAN NUMBERED HEADS TOGETHER BERBASIS STUDENT CREATED CASE STUDIES - Dwi Ayu Lestari (Universitas Islam Negeri Syarif Hidayatullah Jakarta, 2020)
COMPARISON OF STUDENTS' CRITICAL THINKING SKILLS WITH PROBLEM-BASED LEARNING AND NUMBERED HEADS TOGETHER BASED ON STUDENT-CREATED CASE STUDIES MODELS